Role of protein kinase C-gamma in the regulation of lens gap junctions - Das, Satyabrata (Kansas State University, 2009)
The avascular lens tissue depends on the gap junction channels to facilitate intercellular communication for supplying cells deep within the lens with nutrients and removing waste products of cellular metabolism. In the absence of the protein synthesis machinery in the inner lens fiber cells, the proper regulation of gap junction channels becomes extremely important as disturbance of the lens homeostasis can lead to cataract development. Phosphorylation of gap junction subunit connexin proteins has been shown to play an important channel-modulating role in a variety of tissue. Protein kinase C-[Gamma] (PKC[Gamma]) has been implicated in the phosphorylation of connexins in the lens. Here the role of PKC[Gamma] in the regulation of gap junction coupling in the mouse lens has been investigated. We have compared the properties of coupling in lenses from wild type (WT) and PKC[Gamma] knockout (KO) mice. Western blotting, confocal immunofluorescence microscopy, immunoprecipitation, RT-PCR and quantitative real time PCR were used to study gap junction protein and message expression; gap junction coupling conductance and pH gating were measured in intact lenses using impedance studies. PKC[Gamma]was found to regulate the amount and distribution of Cx43 in the lens. Gap junction coupling conductance in the differentiating fibers (DF) of PKC[Gamma] KO lenses was 34% larger than that of WT. In the mature fiber (MF), the effect was much larger with the KO lenses having an 82% increase in coupling over WT. Absence of PKC[Gamma] in the KO mice also caused abnormal persistence of nuclei in the typical nucleus-free region in the DF. These results suggest a major role for PKC[Gamma] in the regulation of gap junction expression and coupling in the normal lens mediated by phosphorylation of the lens connexins. This becomes very vital in the diabetic lenses which contain a depleted amount of PKC[Gamma] and people suffering from spinocerebellar ataxia type-14 (SCA14) who have a mutated inactive form of PKC[Gamma]. Prolonged exposure of lenses to oxidative stress in these patients can lead to cataract formation. In cultured human lens epithelial cells (HLECs), 12-O-tetradecanoylphorbol-13-acetate (TPA) stimulated the depletion of Cx43 protein level via PKC-mediated phosphorylation of Cx43. At the same time Cx46 protein and message levels were upregulated in response to TPA treatment. So, the PKC activator regulates Cx43 and Cx46 in opposing ways. The possible mitochondria localization of Cx46 reported here could help in finding the non-junctional roles for Cx46.
Keywords: Lens; Gap Junctions; Connexin; Protein Kinase C (PKC); Biology, Cell (0379)